2020
DOI: 10.21203/rs.3.rs-104847/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The serological response to SARS corona virus-2 is characterized by frequent incomplete maturation of functional affinity (avidity)

Abstract: The humoral immune systems controls viral infections through recognition of critical viral target structures, selective proliferation stimulation of IgM-presenting B cells, class switch to IgG-generating B cells and subsequent affinity maturation of IgG. Affinity maturation is achieved through proliferation, hypermutation and clonal selection of IgG-generating B cells (1-4). The establishment of high affinity IgG is essential for sustained protective antiviral effects (5-10). While analyzing the maturation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 11 publications
3
19
0
Order By: Relevance
“…The repeated findings on low avidity of IgG directed towards SARS‐CoV‐2 antigens, even several months after onset of clinical symptoms 11,13,14,19–21 ; are unique in viral serodiagnostics so far. Though Luo et al 12 stated that there was a strong correlation between avidity or IgG towards RBD and days after onset of symptoms, their findings are also supporting the findings on low avidity of IgG towards SARS‐CoV‐2 antigens, as the authors had used the very low concentration of 3 M urea in their study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The repeated findings on low avidity of IgG directed towards SARS‐CoV‐2 antigens, even several months after onset of clinical symptoms 11,13,14,19–21 ; are unique in viral serodiagnostics so far. Though Luo et al 12 stated that there was a strong correlation between avidity or IgG towards RBD and days after onset of symptoms, their findings are also supporting the findings on low avidity of IgG towards SARS‐CoV‐2 antigens, as the authors had used the very low concentration of 3 M urea in their study.…”
Section: Discussionmentioning
confidence: 99%
“…The preceding figures have shown that the serological response towards SARS-CoV-2, as well as towards seasonal coronaviruses frequently may enface incomplete avidity maturation, in line with our previous findings. 11 The avidity determination in individual sera therefore does not always allow to immediately distinguish between (i) immature avidity and (ii) low avidity due to just ongoing acute infection. Careful quantitation of avidity in combination with testing a subsequent serum can, however, easily resolve such questions.…”
Section: Kinetics Of Avidity Maturation Of Igg Towards Np Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…Bauer et al, 2021a , defined a mode of analysis that should allow to use avidity determination for the discrimination between acute and past SARS-CoV-2 infections despite low overall avidity. In a follow-up study with 93 sera from 70 SARS-CoV-2-infected Covid-19 outpatients, the frequent incomplete avidity maturation of IgG towards SARS-CoV-2 NP, RBD and S1 was confirmed ( Bauer et al, 2021b ). This study provided evidence that the low avidity found in most cases was due to discontinuous avidity maturation after an initial increase, rather than due to unusually slow avidity maturation.…”
Section: Incomplete Avidity Maturation Of Igg After Natural Infectionmentioning
confidence: 97%
“…The subsequent analysis of outpatients with COVID-19 and SARS-CoV-2 infection confirmed by positive PCR, led, however, to a rather unexpected result ( Bauer et al, 2021a , Bauer et al, 2021b ). In contrast to the regular interaction between the humoral immune system and viruses, the avidity of IgG towards SARS-CoV-2 antigens seemed to remain low in the majority of patients, even several months after the onset of clinical symptoms.…”
Section: Incomplete Avidity Maturation Of Igg After Natural Infectionmentioning
confidence: 99%